2011
DOI: 10.1021/nn203430m
|View full text |Cite
|
Sign up to set email alerts
|

Drug Release from Electric-Field-Responsive Nanoparticles

Abstract: We describe a new temperature and electric field dual-stimulus responsive nanoparticle system for programmed drug delivery. Nanoparticles of a conducting polymer (polypyrrole) are loaded with therapeutic pharmaceuticals and are subcutaneously localized in vivo with the assistance of a temperature-sensitive hydrogel (PLGA-PEG-PLGA). We have shown that drug release from the conductive nanoparticles is controlled by the application of a weak, external DC electric field. This approach represents a novel interactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
329
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(332 citation statements)
references
References 32 publications
0
329
0
3
Order By: Relevance
“…For instance, nanoparticles based on conductive polypyrrole exhibited tailored drug-release profiles as a result of a synergistic process of electrochemical reduction-oxidation and electric-field-driven movement of charged molecules. 160 Zhao et al 161 developed a tunable pH and electro-responsive drug release system based on chitosan-capped MSN. IB-loaded MSNs (IB-MSNs) were dispersed in chitosan solution and co-deposited with chitosan hydrogel on a titanium plate.…”
Section: Electro-responsive Drug Deliverymentioning
confidence: 99%
“…For instance, nanoparticles based on conductive polypyrrole exhibited tailored drug-release profiles as a result of a synergistic process of electrochemical reduction-oxidation and electric-field-driven movement of charged molecules. 160 Zhao et al 161 developed a tunable pH and electro-responsive drug release system based on chitosan-capped MSN. IB-loaded MSNs (IB-MSNs) were dispersed in chitosan solution and co-deposited with chitosan hydrogel on a titanium plate.…”
Section: Electro-responsive Drug Deliverymentioning
confidence: 99%
“…Various types of drug release devices, such as hydrogel, 1,2 nano-particles, 3,4 and membrane-based reservoir devices, [5][6][7][8] have been extensively studied in literature. Among them, pulsatile drug delivery systems (PDDS) have drawn attention as they allow repeatable and reliable drug release flux for clinical needs.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have explored the triggered release of nanoparticles mediated by an electric field [28,29]. In this study, we developed electroresponsive nanoparticles and demonstrated that the triggered-release of PHT from our system was sensitive to an electric field in vitro (as fast as 1 min).…”
Section: Discussionmentioning
confidence: 84%